Internalization of Social Life for The Millennial Generation Through the Qur'an Perspective - Andika Andika; Zainal Fadri; Azhari Maulana (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2022)
The social spirit of society and the values of the Qur'an are two interrelated sides. The current phenomenon shows that the social spirit of society has begun to be fragile and faded for the millennial generation due to the flow of globalization. If one of the two is strengthened then both can be saved. Therefore, this study wants to reveal the values of the Qur'an in the form of the value of brotherhood, the value of knowing each other, the value of equality, and the value of simplicity and generosity contained in the social soul of society. The results of this study indicate that the values of the Qur'an contained in the social soul of the community are able to become a formula for internalizing the social spirit of society for the millennial generation. In the end, this research provides a solution in the form of holding majlis, education, congregational prayers, social harmony forums, and mutual cooperation culture which are considered to be effective solutions in growing the social spirit of society for the millennial